Green Photocatalysis of Organic Pollutants by Bimetallic Zn-Zr Metal-Organic Framework Catalyst - Zhang, Xiaojuan; Yu, Rongfei; Wang, Dandan; Li, Weihua; Zhang, Yutao (Frontiers in Chemistry, 2022)
A series of bimetallic Zn-Zr metal-organic frameworks (Zn-Zr MOFs) with different Zn:Zr molar ratios has been synthesized via a green hydrothermal method. The structures and morphologies of these photocatalysts have been characterized and analyzed by FTIR, XRD, SEM, and nitrogen adsorption-desorption. The prepared Zn-Zr MOFs had large specific surface areas and pore volumes, favoring the adsorption of pollutant molecules, which in turn led to an improved photocatalytic effect. The photocatalytic activities of the Zn-Zr MOFs under visible light irradiation have been studied towards rhodamine B (RhB) as a target pollutant. The extent of degradation of RhB in a 40 mg/L aqueous solution reached 97.4%. The optimal photocatalyst could also degrade other dyes, suggesting a certain degree of universality.